2019
DOI: 10.1016/j.jallcom.2019.06.140
|View full text |Cite
|
Sign up to set email alerts
|

Kondo lattice behavior observed in the CeCu9In2 compound

Abstract: We report systematic studies of CeCu 9 In 2 , which appears to be a new Kondo lattice system. Electrical resistivity exhibits a logarithmic law characteristic of Kondo systems with a broad maximum at T coh ≈45 K and it obeys the Fermi liquid theory at low temperature. Specific heat of CeCu 9 In 2 is well described by the Einstein and Debye models with electronic part at high temperature. Fitting of the Schottky formula to low temperature 4f contribution to specific heat yielded crystal field splitting of 50.2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…42 The binding energies at 906.8 and 885.5 eV are attributed to Ce 3d 3/2 and Ce 3d 5/2 , respectively. 43 For the crystal structure, as we previously reported, 36 these are six cation sites in the YMAS host, including S1. It can be found that these parameters (a, b, c, and V) show an increasing trend with the doping of Eu 2+ and Ce 3+ .…”
Section: ■ Results and Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…42 The binding energies at 906.8 and 885.5 eV are attributed to Ce 3d 3/2 and Ce 3d 5/2 , respectively. 43 For the crystal structure, as we previously reported, 36 these are six cation sites in the YMAS host, including S1. It can be found that these parameters (a, b, c, and V) show an increasing trend with the doping of Eu 2+ and Ce 3+ .…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…The binding energies at 50.1, 74.2, and 102.1 eV are related to Mg 2p, Al 2p, and Si 2p, respectively. , The Eu 3d spectra are composed of two peaks at 1158.3 and 1123.9 eV, ascribed to Eu 3d 3/2 and Eu 3d 5/2 of Eu 2+ , respectively . The binding energies at 906.8 and 885.5 eV are attributed to Ce 3d 3/2 and Ce 3d 5/2 , respectively . For the crystal structure, as we previously reported, these are six cation sites in the YMAS host, including Y and Mg1 (CN = 8, where CN stands for the coordination number), Mg2 and Al1 (CN = 6) and Al2 and Si (CN = 4).…”
Section: Resultsmentioning
confidence: 92%
“…When rare-earth or actinide atoms constitute a sublattice in a compound, the system may be called Kondo lattice compound. The examples may include CeAl 3 [8][9][10], CeCu 2 Si 2 [11][12][13], UBe 13 [14][15][16], CeB 6 [17,18], CeCu 6 [19][20][21], CePtSi [22], Ce 2 PdIn 8 [23], CeGe [24], (Ce 1−x La x )Cu 2 Ge 2 [25], Yb 3 Ru 4 Al 12 [26], UAuBi 2 [27], Ce(Cu, Al,Si) 2 [28], CeCu 2 Mg [29], Ce 2 Rh 3 Sn 5 [30], CeRhIn 5 [31], CeCu 9 In 2 [32], and others. Doniach [33] studied a one-dimensional Kondo lattice model for Kondo lattice compound and suggested that a second-order transition from an antiferromagnetic state to a Kondo spin compensated ground state could occur as the exchange coupling constant J increased to a critical value J c ; for systems in which J ∼ J c , a very weak sublattice magnetization may occur as a result of nearly complete spin-compensation.…”
Section: Introductionmentioning
confidence: 99%